FEATURES OF THE CONCEPT AND CONTENT OF PUBLIC SECURITY - Liliia Muntian (Публічне управління та регіональний розвиток)
The article analyzes the concept of public security in relation to such categories as «security», «national security», «state security», «security of society», «public order». An analysis of the scientific literature on this problem shows that in modern science there are two main approaches to understanding the phenomenon of «public security». Representatives of the first approach define public security as a social state, namely as a state of protection of the vital interests of the individual, society and the state from internal and external threats. Representatives of the second approach understand public security as a system of social relations that develop in the process of protecting the vital interests of the individual, society and the state from internal and external threats. Based on a thorough analysis of the concepts available in modern science, the author's definition of public security was formed.